Constituintes químicos e atividades farmacológicas de Calliandra umbellifera Benth. (Fabaceae) - Silva, Tainá Souza (2013)
The genus Calliandra Benth. belongs to the Fabaceae family and composes 200 species distributed in tropical America, Madagascar and India, being known in Brazil as esponjinhas and can be found in their natural habitat, the Cerrado region, reaching the Caatinga areas in Northeast. Species of this genus are popularly used for kidney pain, cystitis, urethritis, inflammation of the prostate gland, fever and toothache. Calliandra umbellifera Benth is an extincted species that was collected only in Ceará and Piauí and has no reports of popular use, or phytochemical and pharmacological activity. Thereby, this study aimed to contribute with the pharmacognostic studies of Calliandra and Fabaceae through the pharmacological and phytochemical study of Calliandra umbellifera Benth. For this, the plant material was collected in Pico do Jabre (Maturéia - Paraiba) and an exsicata was deposited in the Herbarium Prof. Lauro Pires Xavier (JPB) with code 7430. For the phytochemical study, the vegetable, after drying and pulverization, was submitted to extraction processwith methanol, partition and chromatography for isolating the chemical constituents. The chemical structure of the isolated compounds were elucidated by spectroscopic methods such as InfraRed (IR), Mass Spectrometry (MS) and Nuclear Magnetic Resonance (NMR) of 1H and 13C uni and bi-dimensional and comparisons with literature. From the hexane phase was obtained a mixture of steroids (β-sitosterol and stigmasterol), from the the dichloromethane phase (CH2Cl2) was isolated and identified one aromatic acid: atraric acid, from the ethyl acetate (AcOEt) phase was obtained gallic acid, the pinitol and the iriflofenona glucosyde, the last one being first isolated in the Fabaceae family, and from the phase hydrobutanolic was isolated the mixture of glycosides steroid (β-sitosterol and stigmasterol glycosylated). In the pharmacological study were analyzed the antimicrobial activity of the crude extract, the ethyl acetate and hydrobutanolic phases and the isolated constituents (iriflofenona glycosylated and pinitol), and antinociceptive activity of the crude extract. In antimicrobial activity was observed that the extract and the tested phases show strong antibacterial activity, having established its Minimum Inhibitory Concentration (MIC) between 256 and 128 mg/mL, however showed no antifungal activity. While the isolated compounds (Iriflofenona glycosylated and pinitol) showed no antibacterial activity, however, showed strong antifungal activity, with an MIC of 128 mg / mL. Concerning the antinociceptive activity, the crude methanol extract showed significant activity for the abdominal contractions test induced by acetic acid and for the model of nociception induced by formalin and glutamate, suggesting a possible peripheral analgesic activity.